Data and secondary analysis for High-Precision Machining Behavior of the Single Crystal Scintillator, bismuth germanate (Bi4Ge5O12) - Rogers, Edith; Taieb, Kahina; Belkhir, Nabil; Bizarri, Gregory; Khennab, Abdelghani; Giusca, Claudiu (Cranfield University, 2025)
This data set supports a study on the machinability of a single crystal scintillator, Bismuth Germanate (BGO), a material widely used in Time-of-Flight Positron Emission Tomography (TOF-PET). In this study, the Johnson-Holmquist 2 (JH-2) material model was used to simulate the micro-milling process for BGO. Key parameters for the JH-2 model were estimated from experimental data from quasi-static compression and split tests. Simulations performed using different machining parameters were compared with equivalent machined samples and were able to successfully replicate the conditions observed. This dataset compiles the data and meshes used during the simulations, the compression and split test data, microscopy data for the machined sample, and white light interferometry data used to calculate machined surface roughness and the post-processing required to extract the roughness values.
Simulation data: meshes, input data for the JH-2 model, output graphs for compression tests and milling simulations. Compression tests: experimental stress-strain data for BGO during quasi-static compression and split tests, output graphs and figures 3D microscopy: 2D images and 3D images, CSV files containing 3D data for milled BGO SEM: scanning electron microscopy images taken of milled BGO ra: white light interferometry data collected for milled BGO (proprietory .sur, and .txt (ASCII)); data processing (proprietory Taly Map Gold .mnt file and PDF of workbook); extracted roughness and waviness traces (.csv) and plots (.jpg)
Keywords: Bismuth germanate; time-of-flight positron emission tomography; metascintillator; scintillator; Johnson-Holmquist 2 (JH-2) material model; precision milling; precision machining; stress-strain; milling simulations